Cost Benefit dan Effectiveness Investasi Alat Kesehatan Berteknologi Tinggi di Instalasi Radiologi - Udyanto, Hari Mukti (Jurnal Manajemen, 2021)
One of the important components supporting the effort to cure patients is medical devices. Hermina Mekarsari Hospital type C classification seeks to meet services in accordance with service standards. Preliminary monitoring data found that the CT - Scan examination room facilities in the Radiology Installation have not been used as intended. This is because the medical equipment investment process is not optimal, the financial sector is not involved, so no investment analysis is conducted. The research objective was to analyze the investment feasibility and investment planning process of two CT-Scan and 3D / 4D ultrasound medical devices in Radiology Installation. Research is an empirical study with quantitative methods. The aim is to obtain more in-depth information about the planning process for high-tech and expensive medical equipment. A total of 6 informants as parties involved in the investment process. The results of the study for CT-Scan and 3D / 4D ultrasound, based on NPV calculations are positive, IRR values are lower than the interest rates used, CBR values are more than 1, and PI values are more than 1. It was concluded that from the analysis of financial aspects for investment in both medical devices is worth the investment. It is recommended that hospitals immediately hold the two medical devices in 2020 or 2021.